2021
DOI: 10.1002/mds.28714
|View full text |Cite
|
Sign up to set email alerts
|

ATH434 Reduces α‐Synuclein‐Related Neurodegeneration in a Murine Model of Multiple System Atrophy

Abstract: A BS TRACT: Background: Multiple system atrophy (MSA) is a fatal neurodegenerative disorder characterized by aggregated α-synuclein (α-syn) in oligodendrocytes and accompanied by striatonigral and olivopontocerebellar degeneration and motor symptoms. Key features of MSA are replicated in the PLP-α-syn transgenic mouse, including progressive striatonigral degeneration and motor deterioration. There are currently no approved treatments for MSA. ATH434 is a novel, orally bioavailable brain penetrant small molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…(3) multiple autonomic centers in the brain and spinal cord of PLP-a-syn mice show selective neuronal loss [87][88][89][90]; (4) nigral and striatal neuronal loss feature the underlying motor pathology in PLP-a-syn mice [78]; (5) olivopontocerebellar pathology can be triggered by mitochondrial or proteolytic stress in the PLP-a-syn mouse [85,86]; (6)(7)(8) the neurodegeneration is mediated through gliosis and neuroinflammatory signaling [18,85,112]; (9) early signs of oligodendroglial and myelin dysfunction [95] are accelerated by proteolytic stress [86]; and (10) iron deposition in the degenerating areas can be identified [102,105]. Created with BioRe nder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) multiple autonomic centers in the brain and spinal cord of PLP-a-syn mice show selective neuronal loss [87][88][89][90]; (4) nigral and striatal neuronal loss feature the underlying motor pathology in PLP-a-syn mice [78]; (5) olivopontocerebellar pathology can be triggered by mitochondrial or proteolytic stress in the PLP-a-syn mouse [85,86]; (6)(7)(8) the neurodegeneration is mediated through gliosis and neuroinflammatory signaling [18,85,112]; (9) early signs of oligodendroglial and myelin dysfunction [95] are accelerated by proteolytic stress [86]; and (10) iron deposition in the degenerating areas can be identified [102,105]. Created with BioRe nder.…”
Section: Discussionmentioning
confidence: 99%
“…All relevant current MSA models are based on the assumption that pathological a-syn is the cause of MSA neurodegeneration. On one hand, such a-syn models of MSA are advantageous when testing a-syn targeting treatment strategies, because they provide a clear-cut readout of efficacy based on a-syn pathology modulation [98][99][100][101][102][103][104][105]. Furthermore, the a-syn-based models of MSA provide the possibility to screen targeting of other relevant pathways and disease mechanisms downstream of a-syn pathology like neuroinflammation [18,19,78,106,107], neurotrophic disbalance [108,109], epigenetic impairment [110], or demyelination [97].…”
Section: The Msa Transgenic Mousea Preclinical Therapeutic Testbed Fo...mentioning
confidence: 99%
“…First experiments with novel quinazolinone inhibitor ATH434 (previously known as PBT434) revealed reduced levels of ␣-synuclein and markers of oxidative stress accompanied by motor improvement in PD animal models [69]. Similar results were reproduced in transgenic MSA mice [70,71]. In a phase I study with healthy volunteers, ATH434 was safe and well tolerated (U1111-1211-0052) and achieved CSF concentrations comparable with those associated with efficacy in animal models [72,73].…”
Section: Inhibition Of α-Synuclein Aggregationmentioning
confidence: 97%
“…Anle138b and ATH434 are two compounds tested in an MSA mouse model showing a reduction in protein oligomerization and an improvement of motor symptoms. Phase I clinical trials confirmed the safety of both compounds (Anle138b: NCT04208152), with a phase II trial in MSA patients being prepared to test Anle138b [ 166 168 ]. Immunotherapy is another approach being trialed in MSA and PD patients.…”
Section: Questioning α-Syn: Are We On the Right Track?mentioning
confidence: 99%